Colaboração, cooperação, parcerias: como a reciprocidade afeta o desempenho de organizações sem fins lucrativos - Bozzo, Andréa Luisa (2019)
In this thesis, when contributing to the literature on entrepreneurship orientation (OE), it proposes the characteristic factors of reciprocity and its relation with organizational performance. Conceptually, first, we explore the characteristics of reciprocity as described in the literature and then refine the characteristics of reciprocity, highlighting its relevance as a dimension of OE. The existing research highlights the need to analyze the influence of OE and its dimensions on the performance of organizations and, more importantly, on organizations in specific contexts, such as non-profit organizations. In this research, we analyze how reciprocity can affect the performance of organizations. Empirically, this relationship in the context of nonprofits is explored, which is a relevant context for the specificities, the specific challenges, and the usually smaller allocation of resources and capabilities that characterize NPOs. That is, reciprocity characterizes NPO relationships that can be determinants, possibly more than in other types of traditional organizations, to access a set of complementary resources needed. The data used, of a qualitative nature, were collected through face-to-face interviews, based on the aid of a semi-structured script, with NPO managers and then submitted to content analysis. The findings show that NPOs with reciprocal practices achieve better results differently from NPOs that are less effective in developing reciprocal practices and relationships. The findings also suggest that the characteristics of reciprocity influence performance. In addition, analyzing the many facets that tint reciprocity, collaboration seems to have a greater influence on performance, observing cooperation, partnership, innovation and connection of managers in this process. As a conceptual contribution it is suggested to complement entrepreneurship studies and OE specifically, which allows a better understanding of the actions that configure reciprocity as an OE dimension and its effect on the performance of NPOs. This study thus has managerial implications for the entrepreneurial practices of NPOs, offering subsidies for the members of these organizations to lead actions, aiming at better results.